The Role of Supply Chain Transparency in the Relation between Supply Chain Analytics Capabilities and Firm Performance - Cemberci, Murat; Vural, Suemeyye cicek; Celik, Cemil; Canbaz, Elif (OSCM FORUM, 2024)
Ever-increasing data change the business environment with a great acceleration. This unavoidable data growth brings uncertainties and causes heavy pressure on firms. In this context, supply chain analytics have much more attention in order to manage data in the field of supply chain management. Despite the growing interest in analytics capabilities, the studies are in its early stages. The current study investigated the role of supply chain transparency in the relation between supply chain analytics capabilities and firm performance. The data was gathered via survey from 100 participants from different companies and the PLS-SEM was used in order to investigate theoretical framework. The results indicate that enhanced supply chain analytic capabilities have positive impacts on the firm performance and the supply chain transparency positively moderates this relationship.
Keywords: analytic capability; firm performance; supply chain transparency; BIG DATA ANALYTICS; ORGANIZATIONAL CULTURE; IMPACT; INTEGRATION; STRATEGY; TRUST; Business & Economics